Age group differences in responses to laboratory stressors: task appraisals and affect reactivity - Miller, James Walter, author; Luong, Gloria, advisor; Aichele, Stephen, committee member; Graham, Daniel, committee member (Colorado State University. Libraries, 2022)
Several theories of lifespan socioemotional development posit that adults become more adept at regulating their emotions during stressful situations as they age. However, mixed findings in the literature do not yet provide clear support for this assumption. Cognitive appraisals have been found to influence affective reactivity to stressors, but few studies have directly examined their role in explaining age-group differences in affective reactivity. Additionally, there is limited information available for how trajectories of adaptation in affective reactivity and cognitive appraisals in response to equivalent stressor exposures may vary across adult age-groups. To address these gaps in the literature, the current study used a structural equation modeling framework to examine younger (n = 138) and older adults' (n = 106) trajectories of affective reactivity and cognitive appraisals in response to three exposures to the Trier Social Stress Test. We then investigated the extent to which, over time, changes in cognitive appraisals accounted for age-group differences in changes of affective reactivity. Older adults reported attenuated reductions in negative affective reactivity, smaller decreases in appraisals of task-difficulty, and reduced improvements in appraisals of task-performance, relative to younger adults. Additionally, older adults' appraisals of the task as relatively more difficult over time accounted for their comparatively elevated levels of negative affective reactivity across assessments. Together, these findings suggest that older adults, compared to younger adults, may show attenuated trajectories of adaptation to repeated stressor exposures when the stressor is novel, uncontrollable, or especially threatening to older adults.
Keywords: appraisals; longitudinal; stress; laboratory; age differences; reactivity